Chemical and biostimulant peel with biphasic technology to treat melasma, followed by combined treatments for facial rejuvenation and lifting effect - Massidda, Enrico (Aesthetic Medicine, 2024)
Melasma is a pigmentation disorder of the skin mostly affecting women, especially those with darker skin. It is commonly seen on the face and appears as dark spots and patches with irregular borders. Melasma happens because of an overproduction of the cells that cause skin to have its color. It is harmless, but not easy to treat and present satisfying results. The patient in question was treated for two years every 15 days with a chemical peeling with a biphasic technology. The active ingredients’ dermo-functionality contributed to a profound stimulation of skin replication and biosynthetic processes, essential to counterbalance the effects of skin pigmentation, aging and oxidative damage. During the peeling sessions, treatments with reabsorbable traction threads, with calcium hydroxyapatite (CaHA) filler, with hyaluronic acid filler and with botulinum toxin were performed to reduce skin laxity and increase collagen for skin rejuvenation.